Inheritances and the distribution of wealth or whatever happened to the great inheritance boom? - Edward N. Wolff; Maury Gittleman (European Central Bank (ECB), 2011)
We found that on average over the period from 1989 to 2007, 21 percent of American households at a given point of time received a wealth transfer and these accounted for 23 percent of their net worth. Over the lifetime, about 30 percent of households could expect to receive a wealth transfer and these would account for close to 40 percent of their net worth near time of death. However, there is little evidence of an inheritance “boom.” In fact, from 1989 to 2007, the share of households reporting a wealth transfer fell by 2.5 percentage points. The average value of inheritances received among all households did increase but at a slow pace, by 10 percent, and wealth transfers as a proportion of current net worth fell sharply over this period from 29 to 19 percent or by 10 percentage points. We also found, somewhat surprisingly, that inheritances and other wealth transfers tend to be equalizing in terms of the distribution of household wealth. Indeed, the addition of wealth transfers to other sources of household wealth has had a sizeable effect on reducing the inequality of wealth.
Keywords: D31; J15; 330; household wealth; Inequality; Inheritance; Erbe; Vermögen; Vermögensverteilung; USA